Nilai Nilai Sosial dalam Tradisi Mappanre Temme’ di Kecamatan Tanete Rilau, Kabupaten Barru - Mundzir, Chaerul (Rihlah: Jurnal Sejarah dan Kebudayaan, 2014)
Procession of completing the Qur'an (Khatam), maybe for some people is a common tradition and less interested to be discussed in a study. However, it should be understood that the appreciation of the procedures for completing the Qur'an that make this tradition should be interested to be discussed, because the Qur'an is the major source and soul for all of Muslims. Therefore, it is necessary to explore further the tradition of Mappanre Temme, especially for the Bugis community at the District of Tanete Rilau, Barru. Mappanre Temme’ is a tradition that was born as a result of Islamization at the Kingdom of Tanete in the 17th century and the creativity of the Bugis community also, which was born from the deep Islamization of society. So, it would be appears the appreciation of Procession of completing the Qur'an (Mappanre Temme’ Tradition). Implementation of this tradition isn’t only produce the motivation to continue read the Qur’an. In the end, it should give an effect on the life of society, as in the Mappanre Temme' tradition there are a few of social values to live in the social life now.